The Evaluation of Management Standards on Accreditation Results of PAUD Institutions in 2017 Year (Study of Accreditation Results Documents in BAP PAUD and PNF West Kalimantan) - Hamka Hamka; Wahyudi Wahyudi; M. Chiar (STKIP Singkawang, 2019)
The purpose of this study was to determine the results of accreditation on the standard aspects of PAUD management. This research method uses a documentary study method with a qualitative approach. This type of research in this study is a descriptive case study research. Based on the evaluation recapitulation of all aspects of the management standard that PAUD institutions on average do not yet have a work inspection and assessment document therefore it is a problem that the low achievement period of 8 standards in PAUD units that apply for accreditation in 2017 due to the low 2 aspects PAUD institutions have not yet been launched.